Perfil de resistencia de Pseudomonas aeruginosa y Escherichia coli, aisladas en el Servicio de Medicina Interna del Hospital Nacional Edgardo Rebagliati Martins, octubre-diciembre 2016 - Adrianzén Ramírez, Jilwer Joel (2017)
The present report had as objective to determine the profile of bacterial resistance of Pseudomonas aeruginosa and Escherichia coli in the Internal Medicine Service (10C), the Hospital Edgardo Rebagliati Martins, in the period from october to december 2016. It is a report based on the review of results of antibiograms carried out during the period indicated. The isolation of Pseudomonas aeruginosa were 14, 10 and for Escherichia coli, of the total of positive cultures requested the service. Antibiotics against encountered greater resistance to Pseudomonas aeruginosa were: aztreonam 100%, 92.3% ceftadzidima, piperacillin/tazobactam 91.7%, 84.6%, ciprofloxacin, levofloxacin 71.4%, 64.3%, meropenem, imipenem/cilastatin 57.1%, 28.5% difference of cefepima, tobramycin 21.4%, amikacin 7.1%, 7.1%, colistin gentamicin 0% which show a lower percentage of resistance. In Escherichia coli, antibiotics encountered greater resistance in the group of quinolones with a 90% to 80% to ciprofloxacin and levofloxacin; in the cephalosporins is a resistance of 100% for cefazolin, cefepime, cefotaxime, ceftazidime, ceftriaxone, cefuroxime. In the aminoglycoside resistance was 100% to amikacin, 50% gentamicin; sulfa drugs resistance was 90% for sulfamethoxazole/trimethoprim. In penicillins the ampicillin/sulbactan 100% and 75% to ampicillin; 10 in carbapenems in the lab reports there was resistance to ertapenem, imipenem/cilastatin and meropenem. High resistance of Pseudomonas aeruginosa and Escherichia coli to the antibiotics used in patients of this service was found